RANCANG BANGUN APLIKASI PENGENDALIAN BARANG PADA PT KENCANA GRAHA PERTIWI BERBASIS JAVA - Muhammad Lutfi Agustian; Naely Farkhatin; Randi Ramliyana (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
The purpose of the research is to develop an existing Goods Control application system in order to facilitate data collection and the data collection process of PT Kencana Graha Pertiwi. The research methodology used in the data processing system is a literature study method, namely data collection carried out by taking data from various books in libraries, journals and other books that can be used as a basis for analyzing problems that can be discussed in research, as well as field study methods. namely by making direct observations such as interviews and observations. The system development method used is the Waterfall method. The result of this research is the existence of an application device made with the Java programming language and data storage using a database from MySQL so that the data collection process at PT Kencana Graha Pertiwi becomes more effective, efficient and practical